The Recruitment of External Consultant in Family Business : The Distinctions and Challenges Encountered through Advising Process - Lebedeva, Viktoriya (2021)
Family businesses play a significant role in the overall economic prosperity; therefore, it is crucial to secure their well-being and sufficiency. Advisors or as it is known consultants come out to have a substantial impact on family firms’ development, yet there is a tendency of such companies to be reluctant towards utilizing advising services. The research purpose of this paper is to identify the main challenges experienced by family firms that are preventing them from hiring consultancies along with the favored features of the advisors. After determining the gaps in existing knowledge, the initial goal was interconnected with examining the process of family firms choosing an effective external advisor through several specific phases. Followed by the selection of the qualitative semi-structured interviewing method as the most appropriate one, ten in-depth interviews have been conducted. Subsequently, a content analysis together with a coding technique was applied to the transcribed interviews, resulting in the construction of a tree diagram outlining the most essential categories. The analyzed outcomes suggest several points connected to the topic: the interconnection of commonly addressed matters by family businesses with the firm’s sizing, the declining presence of emotion and relation-based factors across the advising stages, the linkage of soft issues’ relevance to the scope of the consulting project, critical reasoning behind the family firms’ distrust, as well as the dependence of firms’ approaches on the degree of separation between the family and business.